Role of HRCT in detection and characterization of pulmonary abnormalities in pediatric patient’s undergone bone marrow transplant - Tahir Mehmood; Sidra Tahir; Sohail Shahzad; Muhammad Arslan Farooq; Syed Shayan Gilani (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Advancements in transplant regimens, alternative grafts, and new indications have improved bone marrow transplant activity with time. Our objective is to determine the pattern of pulmonary abnormalities using High resolution computed tomography (HRCT) chest scan and to determine the diagnostic accuracy (pulmonary abnormalities) and efficacy (in terms of radiation burden) of HRCT and X-rays after bone marrow transplant.METHODOLOGY: It was a descriptive case series conducted at the department of Radiology, POF Hospital, Wah Cantt over a duration of 8 months (January 2021-Augest 2021). A sample size of 20 patients was calculated using the WHO calculator. Patients were recruited through non-probability consecutive sampling. Patients were undergone through HRCT and chest X-rays for diagnostic accuracy and radiation burden measurement. Data was analyzed using SPSS version 24. Fisher exact test, Receiver Operating characteristic (ROC) Curve analysis and t-test was applied for statistical analysis. p-value ≤0.05 was considered significant.RESULTS: A total of 20 patient’s undergone bone marrow transplants were included in the study. The mean age of patients was 5. 25years.There were 11(55%) male and 9(45%) female in study. Pattern of pulmonary abnormalities was pleural effusion 2(10%) following nodules 1(5%), pneumonia patches 1(5%), ground glass opacities 1(5%) and septal thickening 1(5%). The diagnostic accuracy of HRCT was found to be high as compared to X-rays (88% vs 57% respectively). The mean radiation dose in HRCT and mean radiation dose in X-rays’ indicate a high radiation burden in HRCT (p≤0.001).CONCLUSION: Despite of high radiation burden in HRCT, it had high diagnostic accuracy as compared to X-rays.